The bioherbicidal potential of hemlock water extracts - Jovanović, Vladan D.; Stanojević, Stefan R.; Dmitrović, Slavica S.; Nestorović Živković, Jasmina M.; Nikolić, Bogdan R.; Dragićević, Ivana Č.; Giba, Zlatko (Archives of Biological Sciences, 2025)
Paper description: Plant water extracts are used in agricultural research due to their environmentally friendly preparation and bioactive compounds that can be used in weed control. Conium maculatum water extract (CmWE) cytotoxic effects on weed and one crop species were evaluated. CmWE of dry leaves (50%) inhibited seed germination. CmWE of dry stems (50%) inhibited seed germination of media, A. retroflexus and A. artemisiifolia from 20% to 89%; germination of L. sativa was less affected (9%). CmWE of dry stems (5%) inhibited ragweed germination (45%); germination of Lactuca sativa was unaffected. maculatum water extracts have natural herbicide potential. Abstract: Studying plant species rich in bioactive compounds, including allelochemicals, could lead to the development of biodegradable and environmentally safe herbicides. In this study, a water extract of hemlock (Conium maculatum L.), known to be rich in alkaloids, was used to investigate its effects on the germination of Amaranthus retroflexus L., Ambrosia artemisiifolia L., Stellaria media (L.) Vill., and Lactuca sativa L., providing valuable insights into its phytotoxic properties. Among the C. maculatum water extracts (CmWEs) tested, that of dry leaves showed the strongest inhibitory effect on the germination of all species analyzed. The CmWE of dry leaves (50%) completely inhibited seed germination of all species tested. The CmWE of dry stems (50%) reduced seed germination in S. media, A. retroflexus, and A. artemisiifolia by 20% to 89%, whereas the germination of L. sativa was less affected (9%). In addition, a CmWE of dry stems (5%) selectively inhibited ragweed germination (45%), while the germination of Lactuca sativa was not significantly affected. The CmWE of dry leaves (20%) inhibited early root and shoot growth of S. media more effectively than suppressing seed germination. Moreover, the dry leaves and inflorescences of C. maculatum demonstrate strong allelopathic properties even after two years of storage, highlighting the long-term potential of C. maculatum as a source of natural herbicides.